Tall buildings and sustainability - Oldfield, Philip (2012)
The first decade of the 21st Century can easily be labelled the most active in the 125 year history of the tall building typology, with more, and taller, skyscrapers being constructed than at any other time. This boom in construction has coincided with a global recognition for the need to reduce anthropogenic greenhouse gases with climate change becoming arguably the greatest challenge of the modern world. In light of this, attention has turned towards the environmental impact of tall buildings which are still seen by many as inherently unsustainable.